2017
DOI: 10.1149/2.0421709jes
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a Mathematical Model for the Growth of Anodic TiO2Nanotubes under Constant Current Conditions

Abstract: Due to certain limitations of traditional models, the growth mechanism of porous anodic TiO 2 nanotubes has not been well determined currently. Herein, for the first time, a mathematical model of voltage-time transient curves under constant current conditions is derived theoretically, based on the conception of ionic and electronic currents and Ohm's law. The simulation results show high fidelity to the experimental curves, and illustrate the linear correlation between nanotube length and ionic current. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Open However, based on the ionic current and electronic current theories 31,52,[54][55][56][57][58] and the 'oxygen bubble model', 24,[59][60][61][62] three typical stages in Fig. 1d can be given a clear explanation.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Open However, based on the ionic current and electronic current theories 31,52,[54][55][56][57][58] and the 'oxygen bubble model', 24,[59][60][61][62] three typical stages in Fig. 1d can be given a clear explanation.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%
“…According to the ionic current and electronic current theories, 31,52,[54][55][56][57][58] the formation of anodic TiO 2 nanotubes is a result of the oxide flow around the oxygen bubble. Zhou et al 20 suggested that when the growth of oxide exceeded the rate of the evolution of oxygen bubbles, the viscous flow of oxide around the oxygen bubbles led to the formation of the nanotube embryos.…”
Section: Tio 2 Nanotube Embryos Obtained Under the Preformed Dense Cover Layermentioning
confidence: 99%
See 1 more Smart Citation
“…A new explanation for the decreasing current under low temperature is given based on the 'oxygen bubble model' [32][33][34][35][36][37][38] and the ionic current and electronic current theories. [39][40][41][42][43][44][45] We propose that the electronic current, rather than the eld-assisted dissolution, plays an important role in the growth of nanotubes. During the anodization, the electronic current leads to the formation of oxygen bubbles.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, anodization of aluminum is a well-established electrochemical process performed in mild acid electrolyte solutions that is economical and fully scalable process and requires minimum safety measures. [30][31][32][33][34][35][36] Recent studies have demonstrated that the effective refractive index of NAA can be precisely modulated in a multi-dimensional fashion to create a broad range of PC structures with finely tuned optical properties (e.g. distributed Bragg reflectors, gradient-index filters, bandpass and linear variable bandpass filters, encoded photonic tags, etc.).…”
Section: Introductionmentioning
confidence: 99%